Pengaruh Program Pangan Aman Goes to Campus Batch 4 terhadap Pengetahuan Mahasiswa dan Penerapan CPPOB di UMK Pangan Olahan - Gani, Indriemayatie Asri; Sugiyono, Sugiyono; Rahayu, Winiati P.; Kamila, Athiah (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2026)
Micro, Small, Enterprises (MSEs) of food products in Indonesia face a major challenge related to food safety. To address this issue, one of the Food and Drug Supervisory Agency (BPOM’s) efforts was to launch the Safe Food Goes to Campus (SFGS) program in collaboration with the Ministry of Education, Culture, Research, and Technology. SFGS involved students as agents of change to help business actors understand and implement food safety practices. This research aimed to measure the knowledge of participants regarding good manufacturing practices for processed food (GMP), measure the effectiveness of the SFGS program in fulfilling GMP in MSEs of food products, and develop recommendations for the SFGS program. The research population consisted of 114 SFGS program participants and 114 MSEs of food products. The research was conducted using a survey and a quasi-experimental one-group pre-test post-test design. The data analysis method used a normality test, bivariate analysis, and N-gain test. The results of the analysis showed that SFGS improved students’ know-ledge and had a positive impact on the implementation of GMP in MSEs of food products. Based on the N-gain test, the percentage of the SFGS program effectiveness on students’ knowledge reached 79% for the briefing stage and 90% for the food safety instructor training stage. The application of GMP in MSEs of food products after assistance has in-creased compared to before assistance, as shown by the increase in MSEs of food product Class from D to A by 36%.